An IGF-1 Levels Decrease in SOPK-RI Model Mice After A Low-Carb Diet - Ermawati, Ermawati; Santoso, Budi; Widjiati, Widjiati; Aryani, Hany Puspita (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The aim of this study is to analyze the IGF-1 levels decrease in mice modeled by Polycystic Ovary Syndrome Insulin Resistance post carbohydrate high in protein. True Experimental Design with a Posttest Control Group Design research using 36 tails, female Wistar Rattus Norvegicus Strains, 3 months, 100-200 grams and randomly divided into 3 groups, namely K-(n =12, negative control group), K+(n=12, positive control group) and KP(n=12, treatment group). SOPK-IR modeling is done by mice in the injection of the hormone testosterone provionate at a dose of 100 mg/kg BW for 28 days, on the last day after injection a vaginal swab is performed to identify the condition of diestrus. The measurement of IGF-1 levels used the Enzyme-Linked Immunosorbent Assay method. Data analysis techniques used ANOVA test and LSD post hoc test. The results obtained mean levels of IGF-1 at K- (234.126±32.568) ng/mL, K+ (169.662±30.150) ng/mL, KP (146.528±29.562) ng/mL (p=0.000)